STATUS HEMODINAMIK PASIEN YANG TERPASANG VENTILASI MEKANIK DENGAN POSISI LATERAL KIRI ELEVASI KEPALA 300 - Yuswandi, Yuswandi; Warongan, Anwar Wardi; Rayasari, Fitriani (Journal of Islamic Nursing, 2020)
Changes in position is one of the nursing interventions in the management of patients with mechanical ventilation. Several studies found contradictory effects in different groups of patients. Subiyanto (2018) states that the elevation position of the head 30 degrees lateral left with a time of 5 minutes to 30 minutes has been effective to provide positive changes to the hemodynamic status. But at the Hospital the time used to position the patient is 120 minutes, so it is necessary to know the hemodynamic changes that occur during 120 minute. This studyaaimed to determineathe effective time for the left lateral position of the head elevation of 30 degrees to the hemodynamic status. The research design used was a quasi experimental pre-test-posttest design with a control group. The population was all patients who were installed mechanically at the ICU General Hospital (RSU) Tangerang District in April to July 2019. Samples of 15 respondents in the intervention group and 15 respondents in the control group used purposive sampling technique. Results Estimated significant influence between the left lateral position of the head elevation of 30 degrees to the hemodynamic status on systolic blood pressure P value 0.045, diastolic blood pressure value P 0.001, MAP value P 0.000, Heart Rate value P 0.002 and respiratory rate P value 0.09. There is no effect on SPO2 P value 0.334. No effective time was identified for the implementation of the left lateral position of the head elevation of 30 degrees to the hemodynamic status. in systolic blood pressure, diastolic blood pressure, MAP, Hearth Rate and Respiratory Rate there was a significant increase in the mean value for 120 minutes, while in SPO2 there was a change in the average value of SPO2.Keywords: Left Lateral Position, 300 Head Elevation, Hemodynamic